A novel structural equation modelling-based framework for identifying hydrometeorological multi-factor interaction - Zhongan Li; Xian Guan; Xizhi Nong; Ronghui Li; Lihua Chen; Jiahua Wei (Journal of Hydrology: Regional Studies, 2024)
Study region: The Hanjiang River Basin, China. Study focus: In this study, we proposed a new integrated framework based on structural equation models to identify hydrometeorological multi-factor interaction relationship. The spatiotemporal distribution and interaction relationship of hydrological, meteorological, and vegetation indicators in the Hanjiang River Basin were analyzed based on the national long-series monitoring data. New hydrological insights for the region: The findings reveal that: (1) The rainfall is the maximum in the lower reaches (968.87 mm), and the runoff depth fluctuated the most in the lower reaches (1181.70 mm to 2934.88 mm). (2) Dew point temperature is an important influencing factor of rainfall in the upper and middle reaches, and relative humidity is an important influencing factor of rainfall in the lower reaches. High vegetation cover is an important influencing factor for runoff depth. (3) Rainfall and runoff depth are significantly negatively affected by meteorological characteristics, with effect values ranging from −0.24 to −0.68. However, runoff depth is positively affected by rainfall, relative humidity, vegetation characteristics, and canopy interception, with effect values ranging from 0.02 to 0.58. The size and mode of influence have significant regional differences.